Penerapan pijat oksitosin pada nyonya S dalam Asuhan Kebidanan Masa Nifas di Klinik Pratama Amanda - Achirul Jannah, Latifah; Rahmawati, Isabella; Tri Lestari, Reni (Infomasi dan Promosi Kesehatan, 2022)
Introduction : Lactation is the process of breastfeeding starting from the process of producing breast milk (ASI), secretion, and expulsion of breast milk to the process of the baby sucking and swallowing. Factors that cause non-smooth milk production in primiparous postpartum mothers can be caused by stress, fatigue, lack of rest, as well as nutrition and nutritional factors. Efforts made to improve breastfeeding and increase milk production in primiparous postpartum mothers include a balanced nutritional diet for breastfeeding mothers, early mobilization, oxytocin massage and breast care. Oxytocin massage is one of the efforts made to facilitate milk production for primiparous postpartum mothers. Oxytocin massage done after giving birth can stimulate the release of the hormones prolactin and oxytocin. Purpose: Applying oxytocin massage to breastfeeding on Mrs. S at Amanda Pratama Clinic, Patukan, Ambarketawang, Gamping, Sleman Regency, Special Region of Yogyakarta Methods: The type of research method used is descriptive analytic method. This research instrument used the results of examinations, observations or observations of the author, interviews with clients and supporting data listed in the maternal and child health book owned by the client. Results : The results of research on breastfeeding on Ny. S after doing Oxytocin massage 15-20 minutes every day for 7 days it increased, starting from the first day 90 ml to 680 on day 7. The increase in milk expenditure occurred as much as 88% for 7 days. The biggest increase occurred on the third day. Conclusions: There is an effect of oxytocin massage on breastfeeding in Mrs. S at Amanda Pratama Clinic, Patukan Ambarketawang, Gamping, Sleman Regency, Special Region of Yogyakarta